Aromatic organoarsenic compounds (AOCs) occurrence and remediation methods. (September 2018) - Fei, Jiangchi; Wang, Ting; Zhou, Yaoyu; Wang, Zhenxing; Min, Xiaobo; Ke, Yong; Hu, Wenyong; Chai, Liyuan
Abstract: Many researchers at home and abroad have made a body of researches and have gained great achievements on the environmental occurrence, fate, and toxicity of inorganic arsenic. But there is less research on the use of aromatic organoarsenic compounds (AOCs), which are common feed additives for livestock in the poultry industry. In this review, we outline the current state of knowledge acquired on the occurrence and remediation of AOCs, respectively. We also identify knowledge gaps and research needs, including the elucidation of the environmental fate of AOCs, metabolic pathway, the impact of metabolic modification on toxicity, and advanced analytical or repaired methods that allows for monitoring, identification or removal of the degradation products. Highlights: Aromatic organoarsenic contamination in environment emerged as a serious threat. Various treatment techniques for AOCs removal from water and soil are reviewed. We propose the knowledge gaps to be addressed.